A call to action for new global approaches to cardiovascular disease drug solutions. (13th April 2021) - Figtree, Gemma A; Broadfoot, Keith; Casadei, Barbara; Califf, Robert; Crea, Filippo; Drummond, Grant R; Freedman, Jane E; Guzik, Tomasz J; Harrison, David; Hausenloy, Derek J; Hill, Joseph A; Januzzi, James L; et al.
Abstract: Whilst we continue to wrestle with the immense challenge of implementing equitable access to established evidence-based treatments, substantial gaps remain in our pharmacotherapy armament for common forms of cardiovascular disease including coronary and peripheral arterial disease, heart failure, hypertension, and arrhythmia. We need to continue to invest in the development of new approaches for the discovery, rigorous assessment, and implementation of new therapies. Currently, the time and cost to progress from lead compound/product identification to the clinic, and the success rate in getting there reduces the incentive for industry to invest, despite the enormous burden of disease and potential size of market. There are tremendous opportunities with improved phenotyping of patients currently batched together in syndromic 'buckets'. Use of advanced imaging and molecular markers may allow stratification of patients in a manner more aligned to biological mechanisms that can, in turn, be targeted by specific approaches developed using high-throughput molecular technologies. Unbiased 'omic' approaches enhance the possibility of discovering completely new mechanisms in such groups. Furthermore, advances in drug discovery platforms, and models to study efficacy and toxicity more relevant to the human disease, are valuable. Re-imagining the relationships among discovery, translation, evaluation, and implementation will help reverse the trend away from investment in the cardiovascular space, establishing innovative platforms and approaches across the full spectrum of therapeutic development. Graphical Abstract: